Post-Islamism: The New Face of Political Islam in Indonesia - Huda, Muchammad Nur (Journal Intellectual Sufism Research (JISR), 2021)
Abstract. Movement of Islamic politics in post- Islamism is movement ideology in the discourse of contemporary Islamic studies in Indonesia are being crowded discussed. Post-Islamism first time emerged as the faces of Islam political supporters of the ideology of Islamism in contensasi election of the general governor of Jakarta in 2017 through action to defend Islam on 2nd December 2016 or what is known as the 212 movement. This article aims to examine in detail the emergence of post-Islamism as the new face of political Islam in Indonesia and how post-Islamism is built into a "new manifesto" in the Political Islam movement in Indonesia, based on the reading of political anthropological theory. The method that is used is a literature review by using primary data and secondary. Results of the study showed that the movement of political Islam, post-Islamism, still need further study and comprehensive. The term post- Islamism has not been able to uncover the basic facts about how the terms of the force, lived, and could become the ideological basis for the movement of Islam politics its self.